2019
DOI: 10.12968/ijpn.2019.25.11.542
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nurse–parent relationships in paediatric palliative care: a narrative literature review

Abstract: Background: Paediatric palliative care (PPC) is an active, total approach to the holistic care of the child and family. Close, long-lasting relationships between healthcare professionals and parents in paediatric palliative care enhance quality, provide emotional support and can influence how parents manage their role in the face of uncertainty. Aim: To present a narrative literature review of long-term relationships between children's nurses and parents in PPC settings. Methods: Six databases (CINAHL, PsycINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Parental acceptance of their child's condition and a trusting relationship with a capable HCP were vital prior to initiation. Trusting relationships have been identified in previous research as necessary for parents to participate in planning discussions [15,22,23,30,33,[39][40][41][42]. Generally developing trust is accepted as a gradual process which is better achieved during times of low stress and when the child is stable [43]; however, this study found that parents did not necessarily need to know HCP for a prolonged period to develop the trust and therapeutic alliance required for pACP initiation.…”
Section: Discussionmentioning
confidence: 78%
“…Parental acceptance of their child's condition and a trusting relationship with a capable HCP were vital prior to initiation. Trusting relationships have been identified in previous research as necessary for parents to participate in planning discussions [15,22,23,30,33,[39][40][41][42]. Generally developing trust is accepted as a gradual process which is better achieved during times of low stress and when the child is stable [43]; however, this study found that parents did not necessarily need to know HCP for a prolonged period to develop the trust and therapeutic alliance required for pACP initiation.…”
Section: Discussionmentioning
confidence: 78%
“…Although family can be considered as a helpful strategy for nurse coping surrounding the death of a child or young person, professional confidentiality remains an issue with accessing this type of informal social support. This is echoed in a literature review which recognized the tensions in the closeness and professionalism between nurses and parents of children in palliative care settings (Brimble et al, 2019). This questions the further need for educating AYAC nurses on the risks that leaning too much on friends and family for support may have for them as professionals, as well as those with whom they share their emotional burden, however confidential their disclosures are.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, it helped to understand an event as it had meaning for the patient and it helped deepen the understanding of the patient as a unique individual. This type of care is supportive, personalized, comforting and healing (Brimble et al., 2019; Mojen et al., 2018; Wheeler, 2016; Organization, 2014). Other studies have reported by knowing the patient with a chronic health problem such as cancer, nurses were able to observe and assist in the treatment of basic physical assessment findings.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, it helped to understand an event as it had meaning for the patient and it helped deepen the understanding of the patient as a unique individual. This type of care is supportive, personalized, comforting and healing (Brimble et al, 2019;Mojen et al, 2018;Wheeler, 2016;Organization, 2014). oration and attention to their belief system (Fukumori et al, 2020;Hopia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%